(untitled) (Research, Society and Development, 2020)
Objective: To identify the use of negative pressure therapy and its applicability in Fournier’s Syndrome. Method: This is an integrative literature review, with a descriptive character and a qualitative approach, carried out on the bases PubMed Central and Scientific Electronic Library Online, from August to September 2020. Results: After the establishment of the eligibility criteria, 10 were selected studies, which were analyzed according to the content theme and categorized into: “Negative pressure therapy: use and benefits” and “Use of negative pressure therapy in Fournier’s Syndrome”. Conclusion: Of all the studies selected for the on-screen review, 100% recommended the use of negative pressure therapy, either alone, with instillation or length of stay, to treat wounds resulting from Fournier’s Syndrome, allowing patients less pain, less time hospitalization time, shorter total wound closure time.